2020
DOI: 10.34023/2313-6383-2020-27-1-8-28
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Scale of Illegal Migration in Russia: Possible Approaches and Sources of Information

Abstract: The article discusses various approaches to estimate the scale of illegal migration in Russia, based on the use of administrative data of the Federal Migration Service, the Main Directorate for Migration of the Ministry of Internal Affairs of Russia (MDM) and the Border Service of Russia. It is noted that the problem of assessing illegal migration for the Russian Federation has become very relevant since the late 1990s, when the migration landscape changed, and forced migration flows were replaced by mass labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 1 publication
1
2
0
Order By: Relevance
“…Since 2011, the statistics have been capable of discerning a significant number of long-distance movements. Our calculations basically confirmed the conclusion made by Olga Chudinovskikh [47] who emphasised the catastrophic scale of unrecorded student migration, which was the case until 2011. About 80 % of student migrants, who obtained temporary registration, remained below the radar of statistics.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Since 2011, the statistics have been capable of discerning a significant number of long-distance movements. Our calculations basically confirmed the conclusion made by Olga Chudinovskikh [47] who emphasised the catastrophic scale of unrecorded student migration, which was the case until 2011. About 80 % of student migrants, who obtained temporary registration, remained below the radar of statistics.…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…However, while some studies found a positive relationship between media depictions and fear of migrant crime and anti-immigrant sentiments (Jacobs et al, 2017), others have not found any support for this relationship (Brouwer et al, 2017). Media reports of increased crimes committed by undocumented immigrants occurred in Russia in 2008, and the reports vastly overestimated the figures (Kingsbury, 2017), further legitimizing FMC. The 2012 crime data shows that immigrants were responsible for only 3.5 percent of the total reported crimes, of which nearly a fifth were reported from Moscow and a similar fraction from the outlying areas of Moscow (Golunov, 2014), suggesting a gap in perceptions between the perceived and actual crime by the foreign-born.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, most crimes by foreigners are non-violent (e.g. use of false documents), while crimes against immigrants are often serious (Chudinovskikh, 2018).…”
Section: Introductionmentioning
confidence: 99%